1996
DOI: 10.1021/bk-1996-0653.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Multielectron Reduction of Hydrazine to Ammonia and Acetylene to Ethylene with Clusters That Contain the MFe3S4 Cores (M = Mo, V)

Abstract: Clusters with the [MFe 3 S 4 ] n+ core, (M = Mo, n=3; M = V, n=2). are used as catalysts for the reduction of substrates relevant to nitrogenase function. Substrates such as hydrazine and acetylene, are catalytically reduced by (NEt4)2[(Cl4-cat)(CH3CN)MoFe3S 4 Cl 3 ], I, to ammonia and ethylene respectively, in the presence of added protons and reducing equivalents. Hydrazine also is catalytically reduced by the (NEt4)[(DMF)3VFe3S4Cl 3 ] cubane under similar conditions. Catalysis in excess of 100 turnovers (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…631,[651][652][653] Important new clusters that have been reported include two vanadium clusters with the VS 3 (132), are capable of catalyzing the reduction of hydrazine by cobaltocene/lutidine hydrochloride. 651,[653][654][655] Reduction of hydrazine to NH 3 is commonly used to document the reactivity of these clusters and for the cuboidal clusters (130)(131)(132)(133)(134)(135); the coordination of the hydrazine to the V-atom appears to be critical to its reduction. 630,651,653,655 In contrast to the complexes (129-135) described above, [(HBpz) 3 VFe 3 S 4 Cl 3 ] 2-(136) 653 does not catalyze hydrazine reduction.…”
Section: Clusters In Nitrogenase and Model Systems: Structure And Reamentioning
confidence: 99%
“…631,[651][652][653] Important new clusters that have been reported include two vanadium clusters with the VS 3 (132), are capable of catalyzing the reduction of hydrazine by cobaltocene/lutidine hydrochloride. 651,[653][654][655] Reduction of hydrazine to NH 3 is commonly used to document the reactivity of these clusters and for the cuboidal clusters (130)(131)(132)(133)(134)(135); the coordination of the hydrazine to the V-atom appears to be critical to its reduction. 630,651,653,655 In contrast to the complexes (129-135) described above, [(HBpz) 3 VFe 3 S 4 Cl 3 ] 2-(136) 653 does not catalyze hydrazine reduction.…”
Section: Clusters In Nitrogenase and Model Systems: Structure And Reamentioning
confidence: 99%
“…Apparently, protonation (path 2) of the sulfur donors should be considered as an essential and most promising initial step during the reduction of the dinuclear N 2 complex. [9,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] It is the purpose of this study to investigate this first protonation reduction step in order to obtain a microscopic picture of a possible mechanism of a two-electron reduction of protonated Sellmann-type complexes. A detailed understanding of the reaction mechanism should yield suggestions for a particular ligand sphere for sulfur-rich metal complexes designed to stimulate nitrogen activation.…”
Section: Introductionmentioning
confidence: 99%
“…8 ). In studies by Coucouvanis et al [ 84 , 85 ] [MoFe 3 S 4 ] 3+ cubanes (as well as [VFe 3 S 4 ] 2+ [ 86 ]) were found to be active catalysts for the reduction of hydrazine to ammonia [ 87 , 88 ], acetylene to ethylene [ 89 ] and cis -dimethyldiazene to methylamine [ 90 ]. These studies were conducted using cobaltocene and 2,6-lutidinium chloride as external sources of electrons and protons.…”
Section: Reactivity Of Structural Model Compounds: Relation To Biologmentioning
confidence: 99%